Temporal Effects of High Fishmeal Diet on Gut Microbiota and Immune Response in Clostridium perfringens-Challenged Chickens - Huang, Ting; Gao, Biao; Chen, Wen-Lu; Xiang, Rong; Yuan, Ming-Gui; Xu, Zhi-Hong; Peng, Xin-Yu (Frontiers in Microbiology, 2018)
Necrotic enteritis (NE) caused by Clostridium perfringens is responsible for huge financial losses in the poultry industry annually. A diet highly supplemented with fishmeal is one factor predisposing chickens to the development of clinical NE. However, the effects of fishmeal-rich diets on the gut microbiota and immune response in chickens with C. perfringens challenge over the long-term are not well understood. Here, a chicken NE model was established in which chickens were fed high fishmeal diet and subsequently infected with C. perfringens (FM/CP). Two control groups of chickens, one that was not infected and had a high fishmeal feeding (FM) and another group only infected with C. perfringens with basic diets (CP), were used as comparators. We analyzed the gut microbiota and immune response of the three groups at the age of 20, 24 (1 day post infection, dpi) and 30 days (7 dpi) using 16S rDNA sequencing and real-time PCR, respectively. We found that the composition of the gut microbiota had significant shifted in both the CP and FM/CP groups, although the CP group did not have intestinal lesions. The structure of the gut microbiota in C. perfringens-challenged chickens, independent of a high fishmeal diet, had the tendency to return to their non-infection state if the chickens no longer received C. perfringens challenge. Gut microbiota variation with time in challenged chickens with high fishmeal diet feeding was superimposed upon that of non-infected chickens with high fishmeal feeding. For the immune response, the relative expression of IL-8 in the ileum was significantly higher in infected chickens independent of high fishmeal feeding than in non-infected chickens. However, the expression of alpha 1-acid glycoprotein (AGP) and serum amyloid A (SAA) genes in chicken liver were significantly increased in FM /CP compared to the other groups. In conclusion, high fishmeal feeding induced significant changes to the structure of chicken gut microbiota over time and such changes provided an opening for C. perfringens infection to progress to NE. The relative expression of AGP and SAA in liver tissue may be used as diagnostic biomarkers for poultry NE but such an indication requires further investigation.